2004
DOI: 10.1063/1.1803935
|View full text |Cite
|
Sign up to set email alerts
|

p -type conduction in N–Al co-doped ZnO thin films

Abstract: p -type ZnO thin films have been realized by the N–Al co-doping method. Secondary ion mass spectroscopy demonstrated that the N incorporation was enhanced evidently by the presence of Al in ZnO. The lowest room-temperature resistivity was found to be 57.3Ωcm with a Hall mobility of 0.43cm2∕Vs and carrier concentration of 2.25×1017cm−3 for the N–Al co-doped p-type ZnO film deposited on glass substrate. The results were much better than those for the N-doped p-type ZnO. Moreover, the co-doped film possesses a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
102
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(108 citation statements)
references
References 11 publications
6
102
0
Order By: Relevance
“…Estimated values of film thickness (t) by using Profilometer, gravimetric method and using PARAV software, refractive index at 633nm (n), Energy gap (E g ) and Burstein-Moss energy shift (ΔEBM) for the thin films of B-N codoped ZnO with various B concentrations. 8 and is in agreement with earlier reports 29 . The magnitude of Burstein-Moss energy shift arising from the shift of Fermi levels for the samples were calculated and presented in Table 3.…”
Section: Optical Propertiessupporting
confidence: 83%
See 2 more Smart Citations
“…Estimated values of film thickness (t) by using Profilometer, gravimetric method and using PARAV software, refractive index at 633nm (n), Energy gap (E g ) and Burstein-Moss energy shift (ΔEBM) for the thin films of B-N codoped ZnO with various B concentrations. 8 and is in agreement with earlier reports 29 . The magnitude of Burstein-Moss energy shift arising from the shift of Fermi levels for the samples were calculated and presented in Table 3.…”
Section: Optical Propertiessupporting
confidence: 83%
“…Optical band gaps (E g ) of the deposited thin films are calculated using the Tauc relation 28 (8) where α is the absorption coefficient, hν energy of photon, B is the band tailing parameter and n is a constant equal to 1/2 as ZnO is a direct band material. The plots of (αhν) 2 versus (hν) for the films were shown in Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Techniques used for ZnO film growth include molecular beam epitaxy (MBE), [1] pulsed laser deposition (PLD), [8] metal-organic (MO)CVD, [2] and RF/DC magnetron sputtering. [3] Several groups have even observed electroluminescence at room temperature from ZnO p-n homojunctions, [9][10][11] which is a great step towards the practical application of ZnO optoelectronic devices. It is known that device fabrication requires high-quality crystallinity and abrupt interfaces between epitaxial layers.…”
mentioning
confidence: 99%
“…However, the major component, indium, is one of the expensive rare earth materials components, and will face shortages of natural resources. In order to resolve this drawback in ITO transparent conductors, various materials systems are introduced as a TCO for the replacement of ITO [8][9][10][11][12][13]. Recently, it is reported that electrical conductivity is significantly increased for doped SnO 2 , as well as charge carrier concentration [14,15].…”
Section: Introductionmentioning
confidence: 99%